Editorial - Kaczmarek, Tomasz; Mikuła, Łukasz; Silva, Carlos Nunes (Rozwój Regionalny i Polityka Regionalna, 2022)
The present publication is the result of the conference 'New Challenges of Local Governance in Times of Uncertainty and Complexity', held at the Adam Mickie- wicz University in Poznań, on June 23–24, 2021, organized by the International Geographical Union Commission on Geography of Governance and the Faculty of Human Geography and Planning of the Adam Mickiewicz University. It was the 2022 Annual Conference of the Commission and was organized online due to the COVID-19 pandemic.